Work Fatigue Risk Modeling Based on Environmental, Individual, and Operational Factors in the Coal Mining Industry - Prasetyaningtyas, Sekar Wulan; Hutahaean, Ari Trigar Timotius; Fernando, Eko; Effendi, Siam Arifal (Transpublika Publisher, 2025)
The coal mining industry demands high physical and mental endurance from workers, as they must face exhausting work schedules, heavy activity loads, and high job demands. Previous research has examined factors such as shift work systems, workload, and work environment, but most were conducted separately and have not yet considered the specific context of mining or the role of external factors such as housing conditions. This study aims to analyze the influence of work schedules, work activities, and job demands on fatigue, with housing conditions as a moderating variable. This study uses a quantitative approach with a cross-sectional survey design. Respondents were heavy equipment operators at coal mining contractor companies in East Kalimantan. Of 243 workers surveyed, 213 respondents met the inclusion criteria and were analyzed. Data were collected through questionnaires based on a 1-5 Likert scale and analyzed using PLS-SEM. The research results show that work schedules and work activities have a significant effect on fatigue, while job demands do not show a significant direct relationship. Additionally, housing conditions were proven to significantly moderate the relationship between personal factors and job demands, where better living environments can reduce the negative impact of high demands. These findings emphasize the importance of work schedule management, effective activity planning, and improvement of housing facilities to reduce fatigue levels and enhance worker welfare in the coal mining industry.